The Vaginal and Urinary Microbiomes in Premenopausal Women With Interstitial Cystitis/Bladder Pain Syndrome as Compared to Unaffected Controls: A Pilot Cross-Sectional Study - Meriwether, Kate V.; Lei, Zhenmin; Singh, Rajbir; Gaskins, Jeremy; Hobson, Deslyn T. G.; Jala, Venkatakrishna (Frontiers in Cellular and Infection Microbiology, 2019)
Interstitial cystitis/bladder pain syndrome (ICBPS) may be related to an altered genitourinary microbiome. Our aim was to compare the vaginal and urinary microbiomes between premenopausal women with ICBPS and unaffected controls. This cross-sectional study screened premenopausal women with an O’Leary-Sant questionnaire (ICBPS if score ≥6 on either index; controls <6 on both). Women completed questionnaires on health characteristics, pelvic floor symptoms (OABq, PFDI-20), body image (mBIS), and sexual function (PISQ-IR). Bacterial genomic DNA was isolated from vaginal and clean-catch urinary specimens; the bacterial 16 rRNA gene was sequenced and analyzed using the QIIME pipeline. We performed UniFrac analysis (β-diversity) and generated Chao1 estimator (richness) and Simpson index (richness and evenness) values. We analyzed 23 ICBPS and 18 non-ICBPS patients. ICBPS patients had increased vaginal deliveries, BMI, and public insurance as well as worsened OAB-q, PFDI-20, mBIS, and PISQ-IR domain scores. Lactobacilli was the most abundant genus in both cohorts, and anaerobic or fastidious predominance was similar between groups (p=0.99). For both the urine and vagina specimens, Chao1 and Simpson indices were similar between ICBPS and unaffected women. Weighted and unweighted UniFrac analyses showed no differences between groups. A significant correlation existed between the urinary and vaginal Simpson indices in ICBPS women, but not in unaffected women. Premenopausal women with ICBPS, despite worsened socioeconomic indicators and pelvic floor function, were not found to have significantly different urinary and vaginal microbiomes compared to women without ICBPS.